let f, g be Function of (product (carr G)),REAL; :: thesis: ( ( for x being Element of product (carr G) holds f . x = |.(normsequence (G,x)).| ) & ( for x being Element of product (carr G) holds g . x = |.(normsequence (G,x)).| ) implies f = g )

assume that

A2: for x being Element of product (carr G) holds f . x = |.(normsequence (G,x)).| and

A3: for x being Element of product (carr G) holds g . x = |.(normsequence (G,x)).| ; :: thesis: f = g

assume that

A2: for x being Element of product (carr G) holds f . x = |.(normsequence (G,x)).| and

A3: for x being Element of product (carr G) holds g . x = |.(normsequence (G,x)).| ; :: thesis: f = g

now :: thesis: for x being Element of product (carr G) holds f . x = g . x

hence
f = g
by FUNCT_2:63; :: thesis: verumlet x be Element of product (carr G); :: thesis: f . x = g . x

f . x = |.(normsequence (G,x)).| by A2;

hence f . x = g . x by A3; :: thesis: verum

end;f . x = |.(normsequence (G,x)).| by A2;

hence f . x = g . x by A3; :: thesis: verum